Risk assessment of geological hazards in mountain town scale based on FLO-2D and GIS. Issue 5 (October 2021) - Qiang, Yang; Wang, Gaofeng; Li, Rongjian; Ding, Weicui; Gao, Youlong; Hanle, Le
Abstract: Zhouqu County located in the Bailong River Basin of the Longnan Mountain, which is a high geological-hazard-prone area. This paper constructed the index system and evaluation model of geological hazard evaluation at the scale of town in mountainous area by taking Zhouqu County as an example, which carrying out work of geological hazard zoning, vulnerability assessment and risk assessment used by infinite slope model, Flo-2D and ArcGIS software on the basis of analysing geological conditions. The results show that :(1) Together with considering the slope stability and the threat of debris flow utilize the methods of infinite slope model and Flo-2D software and establishing prediction expression of the maximum sliding distance of landslide by using the detailed sample data of 46 locations in the river basin, which effectively improves the accuracy of hazard assessment.(2) The model of vulnerability evaluation eliminates the evaluation indexes with high repeatability, and selects the main property-type disaster bearing bodies for analysis, evaluation and economic accounting, which greatly improves the evaluation efficiency. (3) The risk assessment results can provide reliable technical support for the territorial spatial planning and disaster prevention and reduction of Zhouqu County as well as provide reference for the risk assessment of geological disasters in other towns in Longnan Mountain Area. (4) In addition to rainfall induced by urban geological disasters in mountainous areas of Bailong River Basin, the impact of earthquakes and human engineering activities cannot be ignored. To achieve the goal of high efficiency, rapid and accurate of the model of urban geological hazard risk assessment, it is necessary to conducts in-depth research on dynamic risk assessment technology and methods.